Activated Zeolites and Heteropolyacids: An Efficient Catalysts for the Synthesis of Triacetoxyaromatic Precursors of Hydroxyquinones - Hadjila, Dokari; Mohamed, Hammadi (Asian Journal of Chemistry, 2013)
The Thiele-Winter reaction is of interest for synthesis of triacetoxyaromatic precursors of hydroquinones. Liquid acid such as, chlorosulfonic acid and solid acids like heteropolyacids have an efficient catalyst can effectively replace sulfuric acid in acetoxylation reaction of quinones without use of organic solvent at room temperature.